2022
DOI: 10.15537/smj.2022.43.5.20220045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonographic features in cancer risk stratification of indeterminate thyroid nodules

Abstract: Objectives: To estimate the risk of malignancy in indeterminate thyroid nodules and to determine whether certain clinical or radiological parameters can predict the risk of malignancy.Methods: This retrospective study enrolled all adult patients )age ≥14 years( with a cytological diagnosis of atypia/follicular lesion of undetermined significance and follicular neoplasm/suspicious for a follicular neoplasm between January 2014 and January 2020. Fifty patients with surgically treated primary thyroid nodules, doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“… 18 Moreover, other investigators have argued that the TI-RADS showed at least some correlation between malignant or benign cytological diagnoses. 3 In contrast, other reports showed that ACR TI-RADS does not help in predicting the ROM in patients with Bethesda III nodules 28 , 29 ; this concurs with our present findings.…”
Section: Discussionsupporting
confidence: 90%
“… 18 Moreover, other investigators have argued that the TI-RADS showed at least some correlation between malignant or benign cytological diagnoses. 3 In contrast, other reports showed that ACR TI-RADS does not help in predicting the ROM in patients with Bethesda III nodules 28 , 29 ; this concurs with our present findings.…”
Section: Discussionsupporting
confidence: 90%
“…26 Our study appears to have a broader scope than many previous studies on AUS. While prior research has primarily focused on clinical and ultrasound (USG) variables or demographic and pathological variables, [27][28][29][30][31] in this study includes a comprehensive examination of clinical, USG, and cytopathological (not routinely examined, all presented in Tables 1 and 2) variables. This comprehensive approach could potentially provide a more detailed understanding of AUS.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found no significant correlation between ROM and age. 2,13,[19][20][21]24 Furthermore, it has been reported that older patients with TNs had a higher ROM. 25 Repeat FNAC.…”
mentioning
confidence: 99%
“…Although the majority of TNs are benign and asymptomatic, the risk of malignant transformation ranges between 5 and 15%. 2 The risk of malignancy (ROM) in a solitary TN ranges from 2.7% to 33%; however, from 1.4% to 10% in a multinodular goiter. Barroeta et al 3 reported that the ROM is equal in one or 2 TNs >1 cm and decreases with ≥3 TNs.…”
mentioning
confidence: 99%
See 1 more Smart Citation